The Effect Of Company Size, Transfer Pricing, And Debt Costs On Tax Avoidance Moderated By Accounting Policy (Study On Manufacturing Companies In Food And Beverage Industry Listed On Indonesia Stock Exchange For The Period 2021-2023) - Janitra Rangga Putra Hervin; Sabaruddin Sabaruddin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of company size, transfer pricing, and debt costs on tax avoidance using accounting policy as a moderating variable. The population of this study consists of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Based on the purposive sampling method, 21 food and beverage manufacturing companies were selected as samples for this study. This research is quantitative in nature, employing descriptive statistical methods. The data in this study were processed using E-Views software. The results of the study show that company size, transfer pricing, and debt costs do not have an effect on tax avoidance. Accounting policy can only moderate the effect of transfer pricing on tax avoidance. Accounting policy weakens the effect of company size on tax avoidance. However, accounting policy cannot moderate the effect of debt costs on tax avoidance. Thus, accounting policy can moderate the effects of company size, transfer pricing, and debt costs on tax avoidance.